Comprehensive analysis of microbial communities in full-scale mesophilic and thermophilic anaerobic digesters treating food waste-recycling wastewater. (July 2018) - Kim, Eunji; Lee, Joonyeob; Han, Gyuseong; Hwang, Seokhwan
Graphical abstract: Highlights: Microbial community structure, dynamics, and diversity were quantified for a year. Defluviitoga (54.6 ± 13.1%) was predominant in thermophilic anaerobic digesters (TD). Methanoculleus (67.7 ± 17.8%) was predominat in mesophilic anaerobic digesters (MD). Methanothermobacter (49.6 ± 11.0%) was the most dominant archaea in the TD. Bacteria and archaea were more diverse in the MD than in the TD. Abstract: Microbes were sampled for a year in a full-scale mesophilic anaerobic digester (MD) and a thermophilic anaerobic digester (TD) treating food waste-recycling wastewater (FRW), then microbial community structure, dynamics and diversity were quantified. In the MD, Fastidiosipila, Petrimonas, vadinBC27, Syntrophomonas, and Proteiniphilum were dominant bacterial genera; they may contribute to hydrolysis and fermentation. In the TD, Defluviitoga, Gelria and Tepidimicrobium were dominant bacteria; they may be responsible for hydrolysis and acid production. In the MD, dominant methanogens changed from Methanobacterium (17.1 ± 16.9%) to Methanoculleus (67.7 ± 17.8%) due to the increase in ammonium concentration. In the TD, dominant methanogens changed from Methanoculleus (42.8 ± 13.6%) to Methanothermobacter (49.6 ± 11.0%) due to the increase of pH. Bacteria and archaea were more diverse in the MD than in the TD. These results will guide development of microbial management methods to improve the process stability of MD and TD treating FRW.